Examine the impact of paralleling two 132/22kv transformers that have a diverse topology considering potential fault event for UTM high voltage network - Abdul Hamid, Mardiha (2021)
Transformer is a magnetically coupled circuit, whose operation is governed by Faraday’s Law of electromagnetic induction. Transformers are also used in AC voltage transfer from one level to another. A step-up transformer raises the voltage from primary to secondary level, while a step-down transformer decreases the secondary to lower voltage. Transformers play a significant role in the power utility as it is the core of the high voltage transmission system. Transformer must always operate without fail and if one transformer fails due to fault, another transformer must take action to supply uninterrupted power (n-1 source) to consumer. To ensure n-1 criteria is met, transformers at transmission level are connected in parallel. To connect transformers in parallel, certain conditions need to be met and the conditions will be discussed in Chapter 1. This study will focus on one of the parallel criteria which is transformer’s topology or as known as vector group. Currently, Universiti Teknologi Malaysia (UTM) high voltage network are installed with two 30MVA 132/22kV transformers of same vector group which is YNd1. It should be no restriction to parallel these two transformers since they have same vector group. To examine the effect of paralleling two transformers of diverse topology, two transformers of different vector will be paralleled using MATLAB Simulink software. This network will then be simulated with potential fault event which in this case, will restrict to only short-circuit fault. This study will extend to analysing the network with the absence of earthing transformer that is connected at secondary side of 132/22kV transformer. Literature studies have also been conducted on the previous parallel transformer scenarios. The results of the simulation will be analysed in order to find out the effect of paralleling transformers with diverse topology. If the result is satisfactory and within limit, it can be applied in electricity industry.